1998
DOI: 10.1002/(sici)1521-4141(199809)28:09<2672::aid-immu2672>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

IL-4-regulated enteropathy in an intestinal nematode infection

Abstract: The relationship between intestinal pathology and immune expulsion of gastrointestinal nematodes remains controversial. Parasite expulsion is associated with intestinal pathology in several model systems and both of these phenomena are T cell dependent. Immune expulsion of gastrointestinal helminth parasites is usually associated with Th2 responses, but the effector mechanisms directly responsible for parasite loss have not been elucidated. In contrast, the intestinal pathology observed in many other disease m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
162
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(176 citation statements)
references
References 38 publications
8
162
3
Order By: Relevance
“…This is the first study that identifies IL-13 as the critical cytokine in the generation of the aberrant intestinal pathology characteristic of nematode infection. A previous study has shown that TNF-␣, under the control of IL-4, is important for villus atrophy and crypt hyperplasia during T. spiralis infection (33). Our study has found that the absence of IL-4 had no effect on tissue architecture or parasite resistance, but suggests that it may be required for optimal goblet cell hyperplasia in concert with IL-13.…”
Section: Discussionsupporting
confidence: 42%
“…This is the first study that identifies IL-13 as the critical cytokine in the generation of the aberrant intestinal pathology characteristic of nematode infection. A previous study has shown that TNF-␣, under the control of IL-4, is important for villus atrophy and crypt hyperplasia during T. spiralis infection (33). Our study has found that the absence of IL-4 had no effect on tissue architecture or parasite resistance, but suggests that it may be required for optimal goblet cell hyperplasia in concert with IL-13.…”
Section: Discussionsupporting
confidence: 42%
“…In contrast to the mouse-T. spiralis model, where enteropathy is rapidly ameliorated after the worms have been expelled in weeks 2 and 3 (Lawrence et al, 1998), here almost complete loss of villi was still evident on day 63 pi (fig. 6) when worms were present.…”
Section: Discussionmentioning
confidence: 76%
“…Much of this analytical work has used the mouse-Trichinella spiralis model and this has generated hypotheses based on immunologically driven mechanisms of enteropathy, both Th2-mediated (Garside et al, 1992;Lawrence et al, 1998) and, more recently, mediated via innate immunity (McDermott et al, 2005). The key parameters quantified in such studies have been villus height, crypt depth and mucosal cellular division as reflected by mitotic figures.…”
Section: Introductionmentioning
confidence: 99%
“…Studies using IL-4 or IL-4-receptor-α deficient mice revealed that IL-4 has a crucial role in worm expulsion [43,44]. However, it is not clear whether IL-5 and/or eosinophils can be implicated in the protective response of the host against the parasite.…”
Section: Protection By Eosinophils In Murine Modelsmentioning
confidence: 99%